1999
DOI: 10.1007/bf02560513
|View full text |Cite
|
Sign up to set email alerts
|

Decline of hepatitis a antibodies during the first 7 months of life in full-term and preterm infants

Abstract: In a previous study we have shown that transplacental transfer of hepatitis A antibodies to preterm infants does not differ from that observed in full-term infants. This follow-up study was designed to investigate the decline of hepatitis A virus (HAV) antibodies during the first 7 months of life in full-term and preterm infants, in an endemic region for hepatitis A. Two hundred and fifty newborn infants--147 full-term and 103 preterm infants--were enrolled. Blood samples from the infants were taken at birth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…These children might have contracted the illness outside the The high prevalence of total anti-HAV (71.4%) in children under 7 months of age who tested negative for IgM anti-HAV strongly suggests passive acquisition of maternal antibodies. However, previous studies have shown that, after 7 months of age, maternal antibodies diminish rapidly, favoring the occurrence of early infection (Vitral et al 1998, Linder et al 1999). In our study, 26.7% of the children aged 7 months to 1 year had already had acute HAV infection.…”
Section: Discussionmentioning
confidence: 98%
“…These children might have contracted the illness outside the The high prevalence of total anti-HAV (71.4%) in children under 7 months of age who tested negative for IgM anti-HAV strongly suggests passive acquisition of maternal antibodies. However, previous studies have shown that, after 7 months of age, maternal antibodies diminish rapidly, favoring the occurrence of early infection (Vitral et al 1998, Linder et al 1999). In our study, 26.7% of the children aged 7 months to 1 year had already had acute HAV infection.…”
Section: Discussionmentioning
confidence: 98%
“…In an endemic area such as Israel, where approximately 50% of newborns have anti-HAV antibodies, it has been shown that at the age of 7 mo only 13% of fullterm infants had protective levels (12). This may justify the vaccination of infants in a region endemic for HAV, as even the initially seropositive infants were primed despite maternal antibody interference (13).…”
Section: Discussionmentioning
confidence: 99%
“…Com isso, Israel tornou-se o primeiro país a instituir um programa nacional de imunização contra a Hepatite A. Nos EUA, a vacinação foi liberada para crianças com mais de 2 anos, mas nas regiões com alta prevalência do vírus A admite-se que a melhor idade para vacinálas é antes de entrarem em contato com o VHA. Estudos feitos por Linder et al 9 mostraram o declínio dos anticorpos maternos no 1º semestre, a utilização da vacina concomitante com DTPa e a resposta positiva à vacina contra hepatite A de lactentes com anticorpos maternos positivos, justificando a vacinação no primeiro ano de vida em regiões de alta prevalência de VHA. A utilização de vacinação universal abre, evi-dentemente, a perspectiva de erradicação da hepatite A no mundo.…”
Section: Hepatite Viral Aunclassified